Bispectral analysis in a patient scheduled for thoracic aortic aneurism surgery: spurious values? - Holanda, Plinio de Oliveira; Pinheiro Júnior, Evaldo José Paes (Brazilian Journal of Case Reports, 2024)
Bisspectral analysis (BIS®) may be the most used way to measure the depth of anesthesia. As a simple device, the monitor can show doctors values captured by a sensor attached to the patient’s forehead. These values vary from zero (very deep anesthesia) to 100 (awake patient). Ideally, BIS® should be between 40 and 60 during general anesthesia, but spurious values have been described in some articles, and in this case report, we show a situation that may never been reported in the literature.